IL1R2 Blockade Suppresses Breast Tumorigenesis and Progression by Impairing USP15‐Dependent BMI1 Stability. Issue 1 (13th November 2019) - Zhang, Lixing; Qiang, Jiankun; Yang, Xiaoli; Wang, Dong; Rehman, Adeel ur; He, Xueyan; Chen, Weilong; Sheng, Dandan; Zhou, Lei; Jiang, Yi‐zhou; Li, Tao; Du, Ying; et al.
Abstract: Breast tumor initiating cells (BTICs) with ALDH + CD24 − CD44 + phenotype are the most tumorigenic and invasive cell population in breast cancer. However, the molecular mechanisms are still unclear. Here, it is found that a negative immune regulator interleukin‐1 receptor type 2 (IL1R2) is upregulated in breast cancer (BC) tissues and especially in BTICs. BC patients with high IL1R2 expression have a poorer overall survival and relapse‐free survival. High IL1R2 promotes BTIC self‐renewal and BC cell proliferation and invasion. Mechanistically, IL1R2 is activated by IL1β, as demonstrated by the fact that IL1β induces the release of IL1R2 intracellular domain (icd‐IL1R2) and icd‐IL1R2 then interacts with the deubiquitinase USP15 at the UBL2 domain and promotes its activity, which finally induces BMI1 deubiquitination at lysine 81 and stabilizes BMI1 protein. In addition, IL1R2 neutralizing antibody can suppress the protein expression of both IL1R2 and BMI1, and significantly abrogates the promoting effect of IL1R2 on BTIC self‐renewal and BC cell growth both in vitro and in vivo. The current results indicate that blocking IL1R2 with neutralizing antibody provides a therapeutic approach to inhibit BC progression by targeting BTICs. Abstract : Interleukin‐1 receptor type 2 (IL1R2) increases BMI1 deubiquitination and stability via binding and enhancing the activity of ubiquitin‐specific protease 15 (USP15) in cell nuclei, intrinsically promoting the self‐renewal of breast tumor initiating cells (BTICs) as well as breast cancer cell proliferation and invasion. Targeting IL1R2 with its neutralizing antibody inhibits the self‐renewal of BTICs, breast tumorigenesis, and cancer resistance to docetaxel.